2020
DOI: 10.1186/s12967-020-02467-w
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning with rHMGB1 ameliorates lung ischemia–reperfusion injury by inhibiting alveolar macrophage pyroptosis via the Keap1/Nrf2/HO-1 signaling pathway

Abstract: Background: Lung ischemia-reperfusion injury (LIRI) is a complex pathophysiological process that can lead to poor patient outcomes. Inflammasome-dependent macrophage pyroptosis contributes to organ damage caused by ischemia/reperfusion injury. Oxidative stress and antioxidant enzymes also play an important role in LIRI. In this study, we conducted experiments to investigate whether and how preconditioning with rHMGB1 could ameliorate LIRI in a mouse model. Methods: Adult male BALB/c mice were anesthetized, the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 37 publications
3
28
0
Order By: Relevance
“…Studies have indicated that endothelial barrier dysfunction is a key factor in ischemia/reperfusion (I/R) injury [ 6 ]. The findings of our previous study were consistent with these other studies as we showed that lung I/R released large amounts of inflammatory factors and induced endothelial barrier dysfunction [ 7 ]. Recent studies also demonstrated that pyroptosis plays a key role in I/R injury [ 8 10 ], although it remains unclear whether pyroptosis is related to LIRI-induced endothelial barrier dysfunction.…”
Section: Introductionsupporting
confidence: 92%
“…Studies have indicated that endothelial barrier dysfunction is a key factor in ischemia/reperfusion (I/R) injury [ 6 ]. The findings of our previous study were consistent with these other studies as we showed that lung I/R released large amounts of inflammatory factors and induced endothelial barrier dysfunction [ 7 ]. Recent studies also demonstrated that pyroptosis plays a key role in I/R injury [ 8 10 ], although it remains unclear whether pyroptosis is related to LIRI-induced endothelial barrier dysfunction.…”
Section: Introductionsupporting
confidence: 92%
“…Moderate pyroptosis can act as a self-protective mechanism against infection, and severe pyroptosis can aggravate lung injury ( Man et al, 2017 ). Fei et al (2020) found that severe pyroptosis was present in a mouse model of lung IRI and inhibited pyroptosis via the alveolar macrophage pathway to ameliorate lung IRI with recombinant high-mobility group box 1. Xu et al (2018) found that in a mouse model of lung IRI, pyroptosis in the lung was more severe 2 h after reperfusion than 1 or 6 h after reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“… 12 Under various pathologic conditions, the strong correlation between oxidative stress injury and nuclear factor E2-related factor 2 (Nrf2) has been previously proved. 13–15 The preceding study has pointed out that Nrf2/HO-1 pathway is one of the most recognized signaling closely associated with oxidative and anti-oxidative balance. 16 , 17 Under normal circumstances, the cap “n” collar subfamily of basic region-leucine zipper transcription factor Nrf2 is restricted in the cytoplasm by binding to its ligand Kelch-like ECH associating protein 1 (Keap1).…”
Section: Introductionmentioning
confidence: 99%